Using Social Networks for Knowledge Acquisition in Regional Australian SMEs: Management Considerations - Evans, Nina; Bosua, Rachelle; Sawyer, Janet (Journal of Knowledge Management Practice, 2013)
Small and Medium Enterprises (SMEs) are important sources of prosperity and employment and are viewed as critical to the economic development of a country. Relationships between SMEs and external stakeholders enable knowledge acquisition and therefore sustainable businesses. Limited research has been done to identify the role of social networks in supporting the acquisition of external knowledge in SMEs in regional areas of Australia. This research explores how SMEs in the Whyalla region of South Australia harness their Social Networks (SNs) to acquire external knowledge and exploit this knowledge to become more innovative. The results are presented as a number of management considerations that will provide useful information to SME managers and bodies such as regional universities and Regional Economic Development Boards, enabling them to support SMEs to create networking and knowledge acquisition opportunities.